Relative lability of trace metals complexed in aquatic humic substances using ion-exchanger cellulose-hyphan - Rocha, Julio Cesar [UNESP]; Toscano, Ilda A. S. [UNESP]; Cardoso, Arnaldo Alves [UNESP] (FapUNIFESP (SciELO), 1997)
The purpose of this paper is to characterize the lability/inertness metal fractions complexed by aquatic humic substances (HS) in relation to pH, complexation time, and HS concentration. HS were preconcentrated by ultrafiltration and complexed with bivalent metal ions. These fractions were characterized by ion exchange with the chelating collector cellulose Hyphan by applying batch procedure. The metals were determined by atomic absorption spectrometry. The results show that the distribution coefficients, Kd, decreased with HS presence, and that the relative lability of metal fractions complexed by HS is dependent on variables such as pH, complexation time, and HS concentration. Until c.a. 15 min, the metal change between aquatic HS and ion exchanger occurs following a 2 order reaction. Afterwards, the remaining metal fraction in the HS reacts following a 1st order reaction. For traces of metal ions bound to dissolved HS, the lability orderPb > Mn > Cd, Ni > Cu is revealed. ©1997 Soc. Bras. Química.
Keywords: Aquatic humic substances; Ion-exchange; Metal complexation